2014
DOI: 10.5713/ajas.2013.13449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Oils on Coccidiosis and Apparent Metabolizable Energy in Broiler Chickens

Abstract: The objective of the present study was to investigate the effects of a mixture of functional oils (Essential, Oligo Basics Agroind. Ltda) on performance response of chickens challenged with coccidiosis and the determination of apparent metabolizable energy (AME), nitrogen-corrected apparent metabolizable energy (AMEn), the coefficients of protein and ether extract digestibility and intestinal morphology of broilers fed with diets containing Essential. In Exp. 1, a completely randomized design (CRD) was used, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 20 publications
3
39
2
Order By: Relevance
“…Similar to our study, Hassan et al (2011) found that the addition of 0.5 and 1% of essential oils to broilers diets, increased villus height significantly. Also, Murakami et al (2014) reported that adding essential oil to the broiler´s ration increased villus height in the jejunum on day 14. In contrast, it was reported that supplementing essential oils to the broiler´s diets had no effect on villus height in the jejunum statistically, but it increased villus height numerically (Jamroz et al, 2006).…”
Section: Citrus Peel Oils Supplementation In Broiler Diet: Effects Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, Hassan et al (2011) found that the addition of 0.5 and 1% of essential oils to broilers diets, increased villus height significantly. Also, Murakami et al (2014) reported that adding essential oil to the broiler´s ration increased villus height in the jejunum on day 14. In contrast, it was reported that supplementing essential oils to the broiler´s diets had no effect on villus height in the jejunum statistically, but it increased villus height numerically (Jamroz et al, 2006).…”
Section: Citrus Peel Oils Supplementation In Broiler Diet: Effects Onmentioning
confidence: 99%
“…However, a few studies have been conducted on supplementing diets with plant extracts to investigate the action mode of active plant oils, morphologically and histologically in animals (Hassan et al, 2011;Murakami et al, 2014). Therefore, the present study was carried out to determine the effects of citrus peel oils (bergamot, orange, lemon) in different levels on performance, jejunum morphology and intestinal microflora in broilers.…”
Section: Introductionmentioning
confidence: 99%
“…Functional oils are defined as oils that have an action beyond their nutritional value (Murakami et al, 2014) and are not derived from essences or spices (Bess et al, 2012), but from oil plants such as castor seeds (Ricinus communis) and cashew nutshell (Anacardium occidentale; Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ltda, www.oligobasics.com.br) containing ricinoleic acid and alkylphenolic oil of the shell of the cashew nut (Anacardium occidentale) showed an improvement in the energy utilization and the livability and decreased lesion caused by coccidiosis (E. acervulina, E.maxima, and E. tenella) in birds treated with Essential [31]. The usage of these plants varies from organic extracts (ethanol, petroleum ether and acetone extracts), ground powder, essential oils, and decoction.…”
Section: Essential Oilsmentioning
confidence: 99%
“…Functional oils comprise those oils that have an action beyond nutritional value [31]. Recently, a variety of essential have been used at different stages of life cycle of Eimeria with good results Figure 6.…”
Section: Essential Oilsmentioning
confidence: 99%